A Neutral Geminal Tin/Phosphorus Frustrated Lewis Pair. Issue 15 (12th March 2019) - Holtkamp, Philipp; Friedrich, Felix; Stratmann, Erik; Mix, Andreas; Neumann, Beate; Stammler, Hans‐Georg; Mitzel, Norbert W.
Abstract: The geminal frustrated Lewis pair (FLP) (F5 C2 )3 SnCH2 P(tBu)2 (2 ) was prepared by reacting (F5 C2 )3 SnCl with LiCH2 P(tBu)2 . It is neutral and contains an extremely electronegatively substituted, but relatively soft (hard–soft acid–base, HSAB) acidic tin function. Its FLP‐type reactivity was proven by reaction with a variety of small molecules (CO2, SO2, CS2, PhNCO, HCl, (Ph3 P)AuCl). However, it shows no reaction in H/D scrambling experiments with H2 /D2 mixtures and binds CO2 reversibly, as was observed by VT‐NMR spectroscopy. Compound 2 and all its adducts were completely characterized by means of multinuclear NMR spectroscopy, elemental analysis, and X‐ray diffraction experiments. Abstract : A soft binding site is provided by the tin atom in the intramolecular frustrated Lewis pair (F5 C2 )3 SnCH2 P( t Bu)2, which forms adducts with a range of small molecules. The softer CS2 binds more strongly, whereas CO2 forms a weaker and reversibly bound adduct.